PENGARUH PROMOSI TERHADAP BRAND IMAGE PADA PENGAMBILAN KEPUTUSAN MENJADI MAHASISWA UNIVERSITAS MERCU BUANA - Ali Hanafiah; Arief Bowo Prayoga Kasmo (Universitas Mercu Buana, 2016)
The purpose of this study was to examine the effect of promotion on brand image to decision to be astudentofUniversity ofMercu Buana.This research have limitation that focus on facultyofeconomicsandbusiness Regular Class in Campus Meruya. With a spread of 259 questionnaires where divided withproportional method are 138 (Management S1), 98 (AccountingS1), 9 (Management D3), 13 (AccountingD3). Based on the results of data processing with AMOS obtained evidence that there is a statisticallysignificantpositiveeffectbetweenPromotionwithBrand Image.Similarly,BrandImagewithDecisiontobeastudentofUniversityofMercuBuanaandPromotionwithDecisiontobeastudentofUniversityofMercuBuana. Moreover, descriptive statistic examine that mostly student of high school knows more about UMBfromattendedoneducationexpo.